Propuesta de proyecto, reglamento y manual de seguridad industrial ocupacional para el taller de la Cooperativa de Transportes Loja de la ciudad de Loja - Vásquez Galarza, Diego Fernando (2015)
At present, the various jobs entail a number of risks, accidents and serious consequences for businesses. It is for this reason that it has become necessary to create rules and regulations for factories, businesses, shops and other places of work, which must be met to prevent accidents and they safeguard human life. For the above named this thesis arose: "PROJECT PROPOSAL REGULATION AND INDUSTRIAL MANUAL FOR OCCUPATIONAL SAFETY WORKSHOP COOPERATIVE TRANSPORTS Loja Loja" The overall objective in this thesis was "a plan of occupational industrial safety for this workshop. Similarly methodologically the study was conducted through a sample survey of 19 workers in the factory of the Cooperativa Loja City Loja. The main results obtained a 84.21% of respondents did not have or there is a greater knowledge management workshop on Occupational Safety Industrial, given that workers are not trained for proper security when performing work activities ; likewise 100% of respondents said that the workshop has no signage, and although there are certain rules and even internal regulations related to this subject is not applied in a practical way. Finally after having performed the analysis was determined to develop a central proposal of occupational industrial safety regulations practical, allowing protect the physical and mental integrity of each shop workers. Based on this background we proceeded to make findings and raise some recommendations are expected to be implemented to increase the safety and health of staff workshop Transportation Cooperative Loja